Anmeldelse: AKUT#5 - Care and Repair - Kröner, Ditte (Dragtjournalen, 2024)
Anmeldelse af udstillingen "AKUT#5 - Care and Repair" på Designmuseum Danmark Reviwe of the exhibition "AKUT#5 - Care and Repair" on Designmuseum Denmark